Hepatocellular carcinoma‐associated single‐nucleotide variants and deletions identified by the use of genome‐wide high‐throughput analysis of hepatitis B virus. Issue 2 (17th August 2017) - Liu, Wen‐Chun; Wu, I‐Chin; Lee, Yen‐Chien; Lin, Chih‐Peng; Cheng, Ji‐Hong; Lin, Yih‐Jyh; Yen, Chia‐Jui; Cheng, Pin‐Nan; Li, Pei‐Fu; Cheng, Yi‐Ting; Cheng, Pei‐Wen; Sun, Koun‐Tem; et al.
Abstract: This study investigated hepatitis B virus (HBV) single‐nucleotide variants (SNVs) and deletion mutations linked with hepatocellular carcinoma (HCC). Ninety‐three HCC patients and 108 non‐HCC patients were enrolled for HBV genome‐wide next‐generation sequencing (NGS) analysis. A systematic literature review and a meta‐analysis were performed to validate NGS‐defined HCC‐associated SNVs and deletions. The experimental results identified 60 NGS‐defined HCC‐associated SNVs, including 41 novel SNVs, and their pathogenic frequencies. Each SNV was specific for either genotype B ( n = 24) or genotype C ( n = 34), except for nt53C, which was present in both genotypes. The pathogenic frequencies of these HCC‐associated SNVs showed a distinct U‐shaped distribution pattern. According to the meta‐analysis and literature review, 167 HBV variants from 109 publications were categorized into four levels (A–D) of supporting evidence that they are associated with HCC. The proportion of NGS‐defined HCC‐associated SNVs among these HBV variants declined significantly from 75% of 12 HCC‐associated variants by meta‐analysis (Level A) to 0% of 10 HCC‐unassociated variants by meta‐analysis (Level D) ( P < 0.0001). PreS deletions were significantly associated with HCC, in terms of deletion index, for both genotypes B ( P = 0.030) and C ( P = 0.049). For genotype C, preS deletions involving a specific fragment (nt2977–3013) were significantly associated with HCC (HCC versus non‐HCC, 6/34 versus 0/32, P = 0.025). Meta‐analysis of preS deletions showed significant association with HCC (summary odds ratio 3.0; 95% confidence interval 2.3–3.9). Transfection of Huh7 cells showed that all of the five novel NGS‐defined HCC‐associated SNVs in the small surface region influenced hepatocarcinogenesis pathways, including endoplasmic reticulum‐stress and DNA repair systems, as shown by microarray, real‐time polymerase chain reaction and western blot analysis. Their carcinogenic mechanisms are worthy of further research. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.